A highly sensitive and rapidly responding fluorescent probe based on a rhodol fluorophore for imaging endogenous hypochlorite in living mice. Issue 5 (11th January 2018) - Zhang, Yanhui; Ma, Lin; Tang, Chunchao; Pan, Shengnan; Shi, Donglei; Wang, Shaojing; Li, Minyong; Guo, Yuan
Abstract : A novel fluorescent probeRO610 was applied for the in vivo detection of endogenous ClO − using living mice. Abstract : Hypochlorous (HOCl) acid is generated as a defense tool in the immune system and plays a vital role in killing a wide range of pathogens. There is therefore great interest in developing fluorescent probes that can endogenously respond to the change in concentration of HOCl in vivo . To address this challenge, we here present a rapidly responding fluorescent probeRO610 to image endogenous HOCl in living mice. The development ofRO610 was based on a novel water-soluble and pH-independent fluorescent xanthene dye, 2′-formylrhodolROA, which exhibits highly selective and sensitive responses to HOCl/ClO − over other reactive species. Moreover, adding a little more than 5 equiv. of ClO − to the solution ofRO610 resulted in a clearly observable fluorescence enhancement (48-fold) within 30 s. Based on these properties, RO610 was used to detect ClO − in A549 cells without interference by other oxidants. It was applied for the imaging of endogenous HOCl in living nude mice with satisfactory results.